2018
DOI: 10.1111/obr.12712
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the evidence for sustained efficacy of dietary interventions for reducing appetite or energy intake

Abstract: We assessed evidence for changes in efficacy of food-based interventions aimed at reducing appetite or energy intake (EI), and whether this could be used to provide guidance on trial design. A systematic search identified randomized controlled trials testing sustained efficacy of diets, foods, supplements or food ingredients on appetite and/or EI. Trials had to include sufficient exposure duration (≥3 days) with appetite and/or EI measured after both acute and repeated exposures. Twenty-six trials met the incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Most of the studies included in our review were carried out using one-off, acute doses monitored for a short period. Sustained exposure to food interventions may elicit body adaptation and provide different responses [ 41 ]. Many of the studies included interventions using small numbers of participants and often only healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies included in our review were carried out using one-off, acute doses monitored for a short period. Sustained exposure to food interventions may elicit body adaptation and provide different responses [ 41 ]. Many of the studies included interventions using small numbers of participants and often only healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Halford et al . (39) recently reviewed the sustained efficacy of products designed to reduce appetite when tested after acute and repeated exposures. They showed that acute robust satiety-enhancing and/or hunger-reducing effects are likely to be sustained.…”
Section: Discussionmentioning
confidence: 99%